Advanced Biomedical and Clinical Diagnostic and Surgical Guidance Systems XIII 2015
DOI: 10.1117/12.2079791
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral fluorescence imaging of human ovarian and Fallopian tube tissue for early stage cancer detection

Abstract: With early detection, five year survival rates for ovarian cancer are over 90%, yet no effective early screening method exists. Emerging consensus suggests that perhaps over 50% of the most lethal form of the disease, high grade serous ovarian cancer, originates in the Fallopian tube. Cancer changes molecular concentrations of various endogenous fluorophores. Using specific excitation wavelengths and emissions bands on a Multispectral Fluorescence Imaging (MFI) system, spatial and spectral data over a wide fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…The second clinical focus of using intraoperative HSI has been to guide tumour resection. The feasibility of using HSI as a diagnostic technique for cancer has been comprehensively evaluated in multiple preclinical animal models and several recent studies have also demonstrated its use in assessing tumour margins in ex vivo tissue in the operating room . Fewer studies have reported the in vivo use of HSI during surgery but several groups have used HSI to highlight subtle changes in exogenous fluorescence .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second clinical focus of using intraoperative HSI has been to guide tumour resection. The feasibility of using HSI as a diagnostic technique for cancer has been comprehensively evaluated in multiple preclinical animal models and several recent studies have also demonstrated its use in assessing tumour margins in ex vivo tissue in the operating room . Fewer studies have reported the in vivo use of HSI during surgery but several groups have used HSI to highlight subtle changes in exogenous fluorescence .…”
Section: Discussionmentioning
confidence: 99%
“…The ability to quantitatively measure oxygenation levels in tissue has been tested in various pathologies and clinical contexts, including; peripheral vascular disease , retinal eye disease , diabetic foot disease and wound healing . Numerous groups have also published work demonstrating the effectiveness of using HSI for cancer detection . With the development of high‐resolution and fast frame rate multispectral and HSI cameras, enabling the capture of a rich imaging dataset at a video rate, these imaging methods offer great potential for real‐time non‐invasive tissue characterization and surgical guidance .…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 24 , 25 Therefore, the optical (reflectance and autofluorescence) signature of STIC lesions is expected to be altered. 22 , 27 Changes in the abundance and accessibility of cell surface receptors and extracellular proteins also occur in STIC and subsequent ovarian cancer, including folate receptors and laminin-C1 proteins, which may be targeted with fluorescence-tagged ligands. 28 , 29 STIC lesions are also characterized by unique cellular and molecular features, and thus could be identified with the use of various cytological or omics analyses.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Optical imaging is a relatively inexpensive, non-ionizing alternative to whole-body imaging and ultrasound that can detect either endogenous changes in reflectance and autofluorescence or the presence of contrast agents and fluorophores targeted to disease-related biomarkers. 22 , 27 , 28 , 31 33 An optical system using reflectance and fluorescence imaging achieved high sensitivity, specificity, and negative predictive value for the detection of clinically occult and cancer-related lesions within ex vivo fallopian tube tissue. However, it had high false-positive rates and therefore low PPV.…”
Section: Introductionmentioning
confidence: 99%
“…Optical imaging techniques that have shown promise for detection of ovarian cancer include fluorescence imaging [5], multispectral imaging [6], confocal imaging [7], MPM [8,9], photoacoustic imaging (PAI) [10], and optical coherence tomography (OCT) [11], among others. Reflectance and fluorescence spectroscopy can differentiate normal and neoplastic ovarian tissue but typically has poor resolution [12]. OCT visualizes details of tissue microstructure such as surface epithelium, follicles, cysts, collagen bundles, and vessels as well as potentially abnormal changes such as invaginations and changes in tissue density, but has inadequate resolution for cellular changes [13,14].…”
Section: Introductionmentioning
confidence: 99%